Incidence, morbidity, mortality and disparities in dementia: A population linked electronic health records study of 4.3 million individuals. Issue 1 (15th March 2022) - Chung, Sheng‐Chia; Providencia, Rui; Sofat, Reecha; Pujades‐Rodriguez, Mar; Torralbo, Ana; Fatemifar, Ghazaleh; Fitzpatrick, Natalie K.; Taylor, Julie; Li, Ken; Dale, Caroline; Rossor, Martin; Acosta‐Mena, Dionisio; et al.
Abstract: Introduction: We report dementia incidence, comorbidities, reasons for health‐care visits, mortality, causes of death, and examined dementia patterns by relative deprivation in the UK. Method: A longitudinal cohort analysis of linked electronic health records from 4.3 million people in the UK was conducted to investigate dementia incidence and mortality. Reasons for hospitalization and causes of death were compared in individuals with and without dementia. Results: From 1998 to 2016 we observed 145, 319 (3.1%) individuals with incident dementia. Repeated hospitalizations among senior adults for infection, unknown morbidity, and multiple primary care visits for chronic pain were observed prior to dementia diagnosis. Multiple long‐term conditions are present in half of the individuals at the time of diagnosis. Individuals living in high deprivation areas had higher dementia incidence and high fatality. Discussion: There is a considerable disparity of dementia that informs priorities of prevention and provision of patient care.